Speech resonance and surgical complications after primary palatoplasty with intravelar veloplasty in patients with cleft lip and palate - Victor Zillo Bosi; Giovana Rinalde Brandão; Renata Paciello Yamashita (Revista Brasileira de Cirurgia Plástica, 2016)
INTRODUCTION: The primary surgical correction of the palate is of fundamental importance in the rehabilitation of individuals with labiopalatine cleft and aims for local anatomical restoration and closure of the existing communication between the nasal and oral cavities, such as functional restoration of the velopharyngeal ring through repositioning of the palatine muscles. Palate closure techniques have evolved progressively over the years and increasingly involve repositioning of the muscles responsible for closing the velopharyngeal sphincter, called intravelar veloplasty. This procedure encourages the synergistic operation of the velar and pharyngeal musculature, thereby avoiding the symptoms resulting from velopharyngeal insufficiency. However, despite efforts to achieve adequate velopharyngeal function, intraoperative events and immediate postoperative and/or late complications may contribute to primary palatoplasty failure and consequently lead to hypernasality. METHODS: Sixty patients underwent primary palatoplasty with intravelar veloplasty. Intraoperative events and immediate and late postoperative complications were investigated. The presence and location of palatal fistula or dehiscence was assessed by clinical evaluation. The patients also made an audio recording of their speech that was analyzed by three speech therapists. The intraoperative events and postoperative complications were descriptively analyzed. The association between intraoperative events and immediate and late postoperative complications with the formation of fistulae as well as that between the occurrence of fistulae and dehiscences and the presence and absence of hypernasality was analyzed using Fisher's exact test. RESULTS: Overall, there was a 5% incidence of intraoperative events, 20% incidence of immediate complications, and 13.3% incidence of late complications. Fistulae and hypernasality were found in 16.67% and 18.6% of cases, respectively. CONCLUSION: Palatoplasty with intravelar veloplasty is a safe and easily implemented technique that is efficient for speech and has low complication rates.